2016
DOI: 10.1128/mbio.01686-16
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal BCG Vaccination Induces Protective Lung-Resident Memory T Cell Populations against Tuberculosis

Abstract: Mycobacterium bovis Bacille Calmette-Guérin (BCG) is the only licensed vaccine against tuberculosis (TB), yet its moderate efficacy against pulmonary TB calls for improved vaccination strategies. Mucosal BCG vaccination generates superior protection against TB in animal models; however, the mechanisms of protection remain elusive. Tissue-resident memory T (TRM) cells have been implicated in protective immune responses against viral infections, but the role of TRM cells following mycobacterial infection is unkn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
234
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(243 citation statements)
references
References 47 publications
7
234
0
2
Order By: Relevance
“…Lymphocytes resident in the lung are sufficient for BCG‐induced protection of mice against M. tuberculosis infection, as blocking egress of cells from the secondary lymphoid organs did not alter the protective effect of the vaccine . Mucosal delivery of BCG in multiple animal models has shown an improvement in protective efficacy compared with parenteral delivery although intriguingly earlier studies showed no difference between vaccination routes . The reason for this difference is unclear but may relate to use of antibiotics to clear bacterial load after immunization in the Palendira study, as it was subsequently identified that vaccine persistence and BCG antigen load impacts T‐cell immunity .…”
Section: New Correlates Of Vaccine‐induced Protection Against Tbmentioning
confidence: 99%
“…Lymphocytes resident in the lung are sufficient for BCG‐induced protection of mice against M. tuberculosis infection, as blocking egress of cells from the secondary lymphoid organs did not alter the protective effect of the vaccine . Mucosal delivery of BCG in multiple animal models has shown an improvement in protective efficacy compared with parenteral delivery although intriguingly earlier studies showed no difference between vaccination routes . The reason for this difference is unclear but may relate to use of antibiotics to clear bacterial load after immunization in the Palendira study, as it was subsequently identified that vaccine persistence and BCG antigen load impacts T‐cell immunity .…”
Section: New Correlates Of Vaccine‐induced Protection Against Tbmentioning
confidence: 99%
“…Given its primary function, inhaled microbes represent a particular challenge, especially host-adapted pathogens like M.tb that have evolved to enter and survive following their entry in the lung where they can get an upper hand early in their pathogenesis. On the other hand, lungs also have uniquely effective clearance capabilities, including rapid recruitment of lymphocytes to the airways and the existence of tissue-resident memory T cells within the lung [88]. Herein we describe several IPs for M.tb as it transits the lung and point out how little we know about these interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these vaccines are expected to elicit an abundant and longer immune response in humans that can induce superior protection against all forms of the disease . Furthermore, it has recently been demonstrated that mucosal or intravenous vaccination with whole‐cell TB vaccines induces a better protection than parenteral vaccination …”
Section: The Clinical Tb Vaccine Candidatesmentioning
confidence: 99%